Quality and safety of pet treats: assessment of the microbial safety and quality of pet treats - Galvão, Julia Arantes [UNESP]; Yamatogi, Ricardo Seiti [UNESP]; Souza Junior, Luiz Carlos Teixeira; Joaquim, Jean Fernandes; Rodrigues, Marianna Vaz [UNESP]; Baldini, Eduardo Delbon [UNESP]; Pinto, José Paes de Almeida Nogueira [UNESP] (Wiley, 2014)
The aim of this study was to evaluate the hygienic and sanitary conditions of pettreats from an export industry. The occurrence of Salmonella, enumerated sulﬁte-reducing Clostridium (SRC), coagulase-positive Staphylococcus (CPS) and total(TC) and thermotolerant coliforms (TTC) was studied. Of the 108 samples ana-lyzed, 22 were contaminated by some microorganism. TC were detected at twosamples (3.5 × 101and 4.5 × 101colony-forming units [cfu]/g), SRC in 19 samples(1.0 × 101to 1.3 × 105cfu/g) and Salmonella spp. at only one sample; CPS andTTC were not detected. These ﬁndings indicate the microbiological safety of mostitems, except for a mix of dried bovine offal, with 1.3 × 105cfu/g of SRC, and onemix of dehydrated bovine viscera contaminated with Salmonella. The current pro-duction processes and the food safety management system are adequate to guar-antee the production of microbiologically safe foods, but that some improvementscan still be made with regard to cleaning and disinfection and hygiene training.